(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The article researches the integrated educational program of the secondary education in Kazakhstan and the content of the textbook of Russian language which was created on its basis for 10 th grades of the natural and mathematical direction. Integrated educational programs being introduced into the Kazakhstan by general education school and it supposed to integrate academic subjects, orientation of learning how to use knowledge to solve problems. The article describes some innovative teaching methods used in the textbook of the Russian language, when language learning is carried out through integration with other subjects through the study of cross-cutting speech topics, the use of texts in various subject areas, the development of academic language.The text in the textbook presents the main didactic unit on the basis of which the skills of working with different types of information are formed, which implies the application of different types of functional reading: introductory (scanning), searching, studying (analytical), commenting.The article provides examples of exercises, tasks that direct the learning process to master functional literacy, which allows students to realize their abilities, successfully adapt and socialize, to develop flexibility of thinking, the ability to evaluate facts objectively, someone’s point of views, to analyze their actions and judgments.The success of the completion of such tasks depends not only on the knowledge of the subject matter but also on the mastery of reading strategies, working with information, its practical application.